Taxonomic revision of the genus Parena Motschulsky, 1860(Coleoptera, Carabidae, Lebiini, Metallicina) - Shi, Hongliang; Liang, Hongbin (Zootaxa, 2023)
The present contribution revises the genus Parena Motschulsky, 1860, a group of arboreal carabid beetles with 46 recognized species, distributed in Tropical Asia, Sub-Saharan Africa, and the north and east coastal Australasia. We re-evaluate the infrageneric taxonomy of the genus and redefine three subgenera: Parena s. str., Bothynoptera Schaum, 1863 and Crossoglossa Chaudoir, 1872, based on the morphological characters of external features, male genitalia and female ovipositors. Under these three subgenera, we define 14 species groups to contain all known species. Keys for the identification of all subgenera, species groups, and species are provided, along with diagnostic characters, included species, geographical distribution, brief discussion on monophyly and relationships for each subgenus and species group, ample species descriptions, distribution maps, habitus images, and genitalia illustrations. The previous alpha-taxonomy of the genus Parena is defective, and several species were described without genital morphological comparisons with their real adelphotaxon. Based on careful examination of a large amount of type materials, we propose 19 new synonyms: P. rufotestacea Jedlička, 1934, as a junior synonym of P. cavipennis (Bates, 1873); P. perforata (Bates, 1873), P. nepalensis Kirschenhofer, 1994, and P. kunmingensis Kirschenhofer, 1996, as junior synonyms of P. dorsigera (Schaum, 1863); P. wrasei Kirschenhofer, 2006, as a junior synonym of P. kurosai Habu, 1967; P. nantouensis Kirschenhofer, 1996 and P. kataevi Kirschenhofer, 2006, as junior synonyms of P. tesari (Jedlička, 1951); P. yunnana Kirschenhofer, 1994, as a junior synonym of P. shapingensis Xie & Yu, 1993; P. albomaculata Habu, 1979, as a junior synonym of P. malaisei (Andrewes, 1947); P. koreana Kirschenhofer, 1994, as a junior synonym of P. monostigma (Bates, 1873); P. phongsalyensis Kirschenhofer, 2011, as a junior synonym of P. quadrisignata Mateu, 1977; P. sellata (Heller, 1921), P. hastata (Heller, 1921), P. sellatoides (Jedlička, 1940), P. fasciata var. unicolor Louwerens, 1949, and P. sumatrana Kirschenhofer, 2011, as junior synonyms of P. fasciata (Chaudoir, 1872); P. nigrolineata nipponensis Habu, 1964 and P. schillhammeri Kirschenhofer, 2006, as junior synonyms of P. nigrolineata (Chaudoir, 1852); and P. alluaudi Jeannel, 1949, as a junior synonym of P. madagascariensis (Alluaud, 1917). Furthermore, the specific status of P. scutata (Alluaud, 1917) is resurrected from synonym with P. plagiata Motschulsky, 1864. Parena sticta (Andrewes, 1947) is excluded from Parena and a new combination is suggested: Peliocypas stictus (Andrewes, 1947) comb. nov. A total of eight new species are described: P. (Crossoglossa) sciakyi sp. nov. (type locality: Guadalcanal, Solomon Islands), P. (Bothynoptera) heteronycha sp. nov. (type locality: Houaphan, Laos), P. (Bothynoptera) emarginata sp. nov. (type locality: Muli, Sichuan, China), P. (Bothynoptera) gonggaica sp. nov. (type locality: Hailuogou, Sichuan, China), P. (Bothynoptera) triguttata sp. nov. (type locality: Kangding, Sichuan, China), P. (Parena) picipes sp. nov. (type locality: Trus Madi, Borneo), P. (Parena) fulva sp. nov. (type locality: Dodoma, Tanzania), and P. (Parena) ruficornis sp. nov. (type locality: Lobaye, the Central African Republic). Several of these new species are very rare in collections, with four of them known from females only.